Gambaran Faktor Pendukung dan Penghambat Dalam Pemberian Asi Eksklusif Di Klinik Laktasi Masa Pandemi Covid-19 - Winda Gaolis Putri Br. Manurung; Yulia Irvani Dewi; Erika (STIKes Payung Negeri Pekanbaru, 2023)
Introduction: Exclusive breastfeeding practices can protect babies from various diseases including COVID-19 and influenced some factors that determine success and failure of exclusive breastfeeding. The purpose of this study was to describe the supporting and inhibitors factors in exclusive breastfeeding during the COVID-19 pandemic. Method: The design of research is descriptive study at Lactation Clinic Pekanbaru. Sample taken by total sampling of 47 mothers who had babies aged 6-12 months. Results: The results showed that mother was not giving exclusive breastfeeding as many as 25 people (53.2%) and exclusive breastfeeding as many as 22 people (46.8%). Supporting factors in exclusive breastfeeding were majority of mother have received high support from health workers 13 people (59.1%), family 17 people (77.3%), and social 11 people (50%). Inhibiting factors in exclusive breastfeeding were physical health of the mother and baby as many as 20 mothers (80%) and 25 babies (100%), psychological mothers was bad as many as 15 people (60%), and socio-culture towards negative 13 people. (52%). Conclusion: That mothers who give exclusive breastfeeding have received high support from various parties such as health workers, families, and social. Barriers mothers not exclusive breastfeeding are health of mother, baby, and socio-cultural.